Legal Protection of Human Rights in the Conflict between Israel and Palestine - Madeira Do Carmo, Giovania; Arum Prastyanti, Rina (International Journal of Social Research, 2024)
This study analyzes the construction of news coverage of the Palestinian-Israeli conflict by NU Online using a framing analysis approach. Focusing on thematic and rhetorical aspects, this study highlights how NU Online influences readers' perceptions through the use of lexicon, details, and coherence in the news text. This research uses a qualitative approach with a constructionism paradigm. Data were obtained through framing analysis of the Zhongdang Pan and Gerald M. Kosicki model, focusing on four framing dimensions: syntax, script, thematic, and rhetorical. The results show that NU Online tends to emphasize the political and colonial aspects of the conflict. This analysis provides insight into how the media shapes complex conflict narratives. It also discusses the dynamics of the conflict between Palestine and Israel and the consensus efforts made through a case study of the 1993 Oslo Peace Agreement. The research highlights the prospects for resolving the conflict, the implications of the peace agreement on the Palestinian people, and the difficulties in implementing the agreement. With a focus on ideological conflicts and territorial rights, this research provides deep insights into the complexity of the Palestinian-Israeli conflict. Legal protection for child victims of war in the perspective of International Humanitarian Law, focusing on the case of Palestinian child prisoners tortured by Israeli soldiers. The article highlights human rights violations, legal protections required for child victims, and sanctions that can be imposed on Israel for violations of International Humanitarian Law.